2022
DOI: 10.3390/ijms23137061
|View full text |Cite
|
Sign up to set email alerts
|

A New Bistable Switch Model of Alzheimer’s Disease Pathogenesis

Abstract: We propose a model to explain the pathogenesis of Alzheimer’s disease (AD) based on the theory that any disease affecting a healthy organism originates from a bistable feedback loop that shifts the system from a physiological to a pathological condition. We focused on the known double inhibitory loop involving the cellular prion protein (PrPC) and the enzyme BACE1 that produces amyloid-beta (Aβ) peptides. BACE1 is inhibited by PrPC, but its inhibitory activity is lost when PrPC binds to Aβ oligomers (Aβo). Exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The positive feedback models proposed earlier by Dupont and De Caluwé [6], and more schematically by Burlando et al [21], similar in some ways to ours, show bistability with a "jump" from a healthy to unhealthy state. This is not the picture seen in our model, which is more like a lifelong steady "drift."…”
Section: Combination Interventionssupporting
confidence: 88%
See 3 more Smart Citations
“…The positive feedback models proposed earlier by Dupont and De Caluwé [6], and more schematically by Burlando et al [21], similar in some ways to ours, show bistability with a "jump" from a healthy to unhealthy state. This is not the picture seen in our model, which is more like a lifelong steady "drift."…”
Section: Combination Interventionssupporting
confidence: 88%
“…The positive feedback models proposed earlier by Dupont and De Caluwé [6], and more schematically by Burlando et al . [21], similar in some ways to ours, show bistability with a “jump” from a healthy to unhealthy state. This is not the picture seen in our model, which is more like a lifelong steady “drift.” We are focused on a transgenic mouse strain designed to demonstrate extreme Aβ accumulation, and the question of bistability might be different in an examination of analogous human data, if and when they become available.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Some studies have suggested signaling pathways by which this might occur. These include m-RNAbased amplification of amyloid precursor protein production [60], feedback loops involving acetylcholine receptors (α7-nAchR) [61], or complex non-linear dynamics involving the prion protein PRP C and cyclic nucleotides [62].…”
Section: Dynamics Of Aβ42 Effectmentioning
confidence: 99%